A Chinese Scholar: WANG DAI YU (1580-1660) His Biography and his efforts for the Development of Islamic Education in China - Ali Nasiruddin (MA HE JU); Abdul Qadir Harun (jihat-ul-islam, 2021)
The article is to study a famous Chinese Muslim scholar: Wang Dai Yu (approx. 1580 - 1660 AD),who is the first Chinese Muslim scholar able to write a series of books concerning deferent aspects of Islamic studies through the styles that was accepted commonly by Chinese scholars and intellectuals in his time, or we can say that he had perfectly used the arts of writing or the methods of expression according to the tradition of Chinese culture, especially Confucianism, in his brilliant scientific and social works. The first part of the article has introduced this great scholar with concerning his birth and death, his family, his teachers, his students, his works and his thoughts. And the second part has concluded the contributions that he had done in the field of Islamic education. The scholar "Wang Dai Yu" is the founder of the Chinese school of Islamic studies, and he is the one that has the most historic role in Islamic spreading and it's education in China.